PSYCHOLOGICAL CHARACTERISTICS ANALYSIS: TOP PLAYERS MOTIVATION APPLIED BY WELL-KNOWN COACHES - Naid Kadušić; Muhedin Hodžić; Alem Kukić (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
Sports psychology, motivation and philosophy are integral part of every team. They make progress in training and contest possible. Psychology helps us to control the mind and body of a player in order to give optimum sporting performance. It is crucial to know how to motivate a player, as well as a team, since a team takes all credits for winning. A special care needs to be taken into account when it comes to preferences, ideas, emotions of players, a team and a coach, of course. There is sports philosphy also, which includes goal setting, behavioural characteristics at the moments of failure, as well as taking into account when, where and at what point to use the philosophy for winning.